Donning the ‘Slow Professor’: A Feminist Action Research Project - Ashencaen Crabtree, Sara; Hemingway, Ann; Sudbury, Sue; Quinney, Anne; Hutchings, Maggie; Esteves, Luciana; Thompson, Shelley; Jacey, Helen; Diaz, Anita; Bradley, Peri; Hall, Jenny; Board, Michele; et al. (Radical Teacher, 2020)
Corporatization of Higher Education has introduced new performance measurements as well as an acceleration of academic tasks creating working environments characterised by speed, pressure and stress. This paper discusses findings from a qualitative, feminist participatory action research (PAR) study undertaken by an interdisciplinary team of women academics at a modern, corporate university in England. The study illuminates how corporatized HE erodes faculty autonomy, degrades learning environments, damages professional satisfaction and health. Strategies for resistance and liberation developed through the PAR process are discussed. Key words: slow professor, corporatized academy, Higher Education.